Increased Autonomic Reactivity and Mental Health Difficulties in COVID-19 Survivors: Implications for Medical Providers - Dale, Lourdes P.; Cuffe, Steven P.; Kolacz, Jacek; Leon, Kalie G.; Bossemeyer Biernacki, Nadia; Bhullar, Amal; Nix, Evan J.; Porges, Stephen W. (Frontiers in Psychiatry, 2022)
Background: Because there is a relationship between mental health (MH) and medical adversity and autonomic dysregulation, we hypothesized that individuals infected with COVID-19 would report greater current autonomic reactivity and more MH difficulties (emotional distress, mindfulness difficulties, and posttraumatic stress). We also hypothesized that COVID-19 infection would strengthen the relationship between prior adversity and current (MH) difficulties, and that medical providers caring for COVID-19 patients would be more negatively impacted due to their increased stress and infection rates. Method: US participants (N = 1638; 61% female; Age M = 46.80) completed online measures of prior adversity, current autonomic reactivity and current MH difficulties, and COVID-19 diagnosis history. Participants diagnosed with COVID-19 (n = 98) were younger and more likely to be providing medical care to COVID-19 patients. Results: Individuals diagnosed with COVID-19 reported increased current autonomic reactivity, being more negatively impacted by their prior MH/medical adversities, and currently experiencing more MH difficulties with an increased likelihood of clinically-significant PTSD and depression (p < .01 – p < .001). Current autonomic reactivity mediated 58.9% to 85.2% of the relationship between prior adversity and current MH difficulties; and COVID-19 diagnosis moderated and enhanced the effect of prior adversity on current autonomic reactivity (p < .01). Being a medical provider was associated with increased current autonomic reactivity (p < .01), while moderating and enhancing the relationship between current autonomic reactivity and emotional distress and posttraumatic stress symptoms (p < .05). Combining COVID-19 diagnosis with being a medical provider increased likelihood of clinically-significant PTSD and depression (p < .01). Conclusion: Individuals diagnosed with COVID-19, particularly medical providers, have increased current autonomic reactivity that is associated with their prior adversities and current MH difficulties.